Optimalisasi Pemeliharaan Jalan Wilayah I Dinas Binamarga, Cipta Karya dan Tata Ruang Provinsi Sumatera Barat - Eva Rita; Nasfryzal Carlo; Khairul Anwar (Universitas Batanghari Jambi, 2023)
The occurrence of road damage causes road conditions to be less stable. This was triggered by the ineffective implementation of road maintenance in Region I Dinas Binamarga, Cipta Karya, and Tata Ruang provinsi Sumatra Barat. For this reason, efforts and strategies are needed so that road maintenance work becomes optimal and the road can reach the specified design age so that the road in question can be used safely, comfortably, and safely. To obtain the intended solution, a study was carried out on what factors influenced the effectiveness of road maintenance in area I of the Highways, Human Settlement, and Spatial Planning Offices of West Sumatra Province. This study uses descriptive qualitative and evaluative methods through literature study and primary data collection by interviewing predetermined informants. Halil's study shows that there are nine factors for the effectiveness of road maintenance, namely responsiveness, responsibility, community support, funds/budgets, time, human resources, coordination between policymakers, organizational effectiveness, and material resources. There are three dominant factors influencing the effectiveness of road maintenance, namely funds/budget, time, and human resources. SWOT analysis is used to determine the optimal solution to obtain the weight of the IE diagram (x, y = -0.85, -0.425) so that the proposed strategy is to maintain and maintain the existing system by carrying out periodic road damage surveys to find out damage so that potential damage and how to handle it, calculating budget requirements, determining priority scales for road maintenance, determining patterns of work implementation either by self-management or in collaboration with third parties, or collaboration with local communities, placing competent and experienced personnel and adjusting the number of road observers with the length of the existing roads.